The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1143/jjap.47.7160
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple-Layer Write-Once Disk for Blue Laser Based on Te–O–Pd Recording Films

Abstract: The excellent performance of a 100-GB-capacity write-once disk was demonstrated. The disk has quadruple recording layers, i.e., Layer 3, 2, 1, and 0 (from the laser-incident side of the disk) based on the 4Â Blu-ray disc (BD) format. Each layer is provided with a phase-change type memory film of Te-O-Pd, whose thickness was 20 nm for Layer 0, and only 6 nm for Layers 1, 2, and 3 in order to obtain high transmissivity. Additionally, for Layers 2 and 3, a metallic reflection layer was not needed and an AlN film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…For example, a four layer system based on the Blu-Ray DiskÔ format recorded 100 Gbyte on a single disk. 18 Efforts to increase storage density further have moved in the direction of shorter wavelengths and layered structures. Using optical sectioning technologies for reading and writing, 19 as many as 16 layers can be written into a 80 mm thick material using two photon methods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a four layer system based on the Blu-Ray DiskÔ format recorded 100 Gbyte on a single disk. 18 Efforts to increase storage density further have moved in the direction of shorter wavelengths and layered structures. Using optical sectioning technologies for reading and writing, 19 as many as 16 layers can be written into a 80 mm thick material using two photon methods.…”
Section: Introductionmentioning
confidence: 99%
“…The melting point of Si is 1414°C while the Cu-Al alloy utilized in this study melts at about 1045°C. Furthermore, thermal simulation studies of optical disks [15][16][17][18] indicated the disk sample is unlikely heated over 800°C at P w = 7.9 mW for the 4ϫ recording performed in this work. Instead of melting induced by laser irradiation, the Cu-Al/Si layer should thus experience a heating process similar to the rapid thermal annealing.…”
Section: Characterization Of Write-once Blu-ray Disk Containing Cu-almentioning
confidence: 90%
“…In contrast, Blu-ray disc records the data by physical change to a recording layer medium, which is an irreversible process and almost impossible to tamper with the data.  High-durability and long-term preservation of data for more than 50 years [4]. Blu-ray disc is covered with a transparent protective layer on the recording layer, which makes it resistant to changes in the external temperature, humidity and light.…”
Section: Development and Advantages Of Optical Storagementioning
confidence: 99%